2017
DOI: 10.1002/2016wr020344
|View full text |Cite
|
Sign up to set email alerts
|

The influence of evaporation and rainfall on supratidal groundwater dynamics and salinity structure in a sandy beach

Abstract: Evaporation has been recognized as a major driving force affecting coastal aquifer systems. However, its effects on subsurface flow and salinity structure have not been investigated in sufficient detail. This paper presents field measurements and numerical simulations of pore water flow and subsurface salinity structure in the supratidal zone of a sandy beach subjected to evaporation as well as rainfall. It was found that evaporation significantly increased pore water salinity, up to 85 g/L, within a shallow l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 59 publications
3
22
1
Order By: Relevance
“…Tidally-driven SGD has been extensively investigated following the discovery of the beach water table over-height or super-elevation (Nielsen, 1990) followed by the discovery of fresh groundwater tubes underlying upper saline plumes in beach aquifers (Robinson et al, 2006). Seawater infiltrating beaches, fractured aquifers and/or marshes at high tide creates a circulation cell that drives the return of seawater to the ocean at low tide on time scales of days to months (Robinson et al, 2009;Wilson et al, 2015;Geng and Boufadel, 2017;Santos et al, 2019). This process can account for a large fraction of SGD on a local scale, releasing solutes from the beach into the ocean.…”
Section: Geophysical Processesmentioning
confidence: 99%
“…Tidally-driven SGD has been extensively investigated following the discovery of the beach water table over-height or super-elevation (Nielsen, 1990) followed by the discovery of fresh groundwater tubes underlying upper saline plumes in beach aquifers (Robinson et al, 2006). Seawater infiltrating beaches, fractured aquifers and/or marshes at high tide creates a circulation cell that drives the return of seawater to the ocean at low tide on time scales of days to months (Robinson et al, 2009;Wilson et al, 2015;Geng and Boufadel, 2017;Santos et al, 2019). This process can account for a large fraction of SGD on a local scale, releasing solutes from the beach into the ocean.…”
Section: Geophysical Processesmentioning
confidence: 99%
“…Compared to tides, waves have been characterized as high‐frequency oscillations whose breaking causes very complicated energy dissipation along beach surface; they, thus, cause high‐frequency seawater‐groundwater recirculation along the swash and surf zones of coastal beaches with large spatial and temporal variations (Bakhtyar et al, ; Geng, Heiss, et al, ; Geng & Boufadel, ; Heiss et al, ; Longuet‐Higgins & Smith, ; Xin et al, ). Evaporation could be also an important driver, altering coastal groundwater flow and causing solute (e.g., salt) accumulation near the beach surface (Geng, Boufadel, & Jackson, ; Geng & Boufadel, ).…”
Section: Introductionmentioning
confidence: 99%
“…The swash zone, defined as that part of the beach between the wave run-down and run-up limits, has been recognized as a very dynamic region in coastal aquifer systems due to high-frequency inundation and infiltration by individual waves (Geng & Boufadel, 2017;Geng et al, 2016a;Horn, 2006;Robinson et al, 2009;Spiteri et al, 2008). Previous studies have revealed significant influences of seawater infiltration and associated mixing with groundwater on the geochemical conditions and chemical fate in nearshore beach aquifers (Jelgersma et al, 1995;Pezeshki et al, 1990;Ranjan et al, 2006;Robinson et al, 2009;Spiteri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%